Effects of rearing system (floor vs. cage) and sex on performance, meat quality and enteric microorganism of yellow feather broilers - Lai-di WANG; Yang ZHANG; Ling-ling KONG; Zhi-xiu WANG; Hao BAI; Yong JIANG; Yu-lin BI; Guo-bin CHANG; Guo-hong CHEN (Journal of Integrative Agriculture)
This study investigated the effects of floor and cage rearing systems on performance, meat quality, and enteric microorganisms of male and female yellow feather broilers. Two hundred Xueshan chickens (42 days old; 100 of each sex) were divided into four groups, according to sex and rearing system (stainless-steel cage or litter floor). Male and cage-reared broilers exhibited better (P<0.001) performance and higher (P≤0.001) eviscerated percentage than female and floor-reared broilers. The interaction between rearing system and sex had an effect (P<0.05) on the percentage of breast and thigh muscles. Female floor-reared broilers presented the highest (P<0.02) percentage of breast and thigh muscles among all the groups. In both sexes, the abdominal fat content in cage-reared broilers was higher (P<0.01) than that in floor-reared broilers. Female cage-reared broilers exhibited better (P<0.05) meat quality of breast muscle than other groups. An analysis of welfare observations indicated that the feather quality of floor-reared broilers was better (P<0.01) than that of cage-reared broilers, whereas the gait scores were not significantly affected (P>0.05) by rearing system. The enteric microbiota assessment by 16S rRNA amplicon-based sequencing showed that Firmicutes, Proteobacteria, and Bacteroidetes were the most prevalent phyla in both rearing systems, and that the cecum was relatively stable in terms of microbiome composition. Floor-reared broilers exhibited a richer diversity of bacteria in the intestinal tract than cage-reared broilers, while alpha diversity was not significantly different (P>0.05) among the groups. The ratio of Bacteroidetes to Firmicutes and the abundance of Helicobacter and Romboutsia could potentially affect the production of broilers. These findings indicate that cage rearing improved the production of male Xueshan broilers, which may be due to the difference in enteric microbiota between cage and floor rearing systems.